2008
DOI: 10.1051/fruits:2008024
|View full text |Cite
|
Sign up to set email alerts
|

Calcium induces salinity tolerance in pistachio rootstocks

Abstract: --Introduction. Saline soils may exert a different effect on seed germination and seedling growth. Materials and methods. The seeds of two rootstocks of pistachio (Pistacia vera), Ghazvini and Badami-e-zarand, were incubated at 20°C in the dark in a 150 mM NaCl solution or in 150 mM NaCl solutions amended with (50, 100 and 150) mM CaSO 4 . Seeds were planted in pots containing a mixture of garden soil, sand and compost (1/3 v/v) to investigate the effect of calcium sulphate on plants grown under salt stress. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 44 publications
4
9
0
3
Order By: Relevance
“…The growth and biomass of pistachio genotypes reduced with increasing NaCl concentration in the nutrient solution. This was in accordance with the earlier reports on studying pistachio responses to salt stress (Hokmabadi et al, 2005;Tavallali et al, 2008;Karimi et al, 2009). Limitation of plant growth under salt stress can be attributed to osmotic stress, leaf injuries, and reduced photosynthesis active area (Wahome et al, 2001).…”
Section: Plant Growthsupporting
confidence: 93%
“…The growth and biomass of pistachio genotypes reduced with increasing NaCl concentration in the nutrient solution. This was in accordance with the earlier reports on studying pistachio responses to salt stress (Hokmabadi et al, 2005;Tavallali et al, 2008;Karimi et al, 2009). Limitation of plant growth under salt stress can be attributed to osmotic stress, leaf injuries, and reduced photosynthesis active area (Wahome et al, 2001).…”
Section: Plant Growthsupporting
confidence: 93%
“…In the current experiment, chlorophyll loss by salinity was higher in Fuji/MM106 plant. Tavallali et al (2008) reported similar result that salinity declined chlorophyll.…”
Section: Discussionsupporting
confidence: 56%
“…Chlorophyll biosynthesis is a conspicuous process that is necessary for photosynthesis. Chlorophyll is made from 5-aminolaevulinic acid (ALA) (Beale 1999) that was reported to decrease in salt stressed plant leaves (Santos 2004;Tavallali et al 2008). Moreover, the decrease in chlorophyll content may be due to an increase in chlorophyll degradation and/or decrease in mineral acquisition needed for chlorophyll synthesis (El-Desouky and Atawia 1998).…”
Section: Discussionmentioning
confidence: 99%